2021
DOI: 10.1186/s12879-021-06401-3
|View full text |Cite
|
Sign up to set email alerts
|

Serological and molecular epidemiology of the Dengue, Zika and Chikungunya viruses in a risk area in Brazil

Abstract: Background The co-circulation of types of arbovirus in areas where they are endemic increased the risk of outbreaks and limited the diagnostic methods available. Here, we analyze the epidemiological profile of DENV, CHIKV and ZIKV at the serological and molecular level in patients with suspected infection with these arboviruses in the city of Juazeiro do Norte, Ceará, Brazil. Methods In 2016, the Central Public Health Laboratory (LACEN) of Juazeiro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…In this first performance evaluation study, VIDAS ® anti-CHIKV IgM and IgG results were comparable to those of competitor IgM and IgG ELISAs, with positive and negative agreements between 97.5% and 100.0%. Given that existing commercial anti-CHIKV IgM and IgG ELISA are recognised for their ability to accurately detect anti-CHIKV antibodies [5,6,10,11,19,20,[22][23][24], our study, therefore, demonstrates the good clinical performance of the VIDAS ® anti-CHIKV IgM and IgG assays. Our study also confirmed the superior performance of ELISA over RDT, in accordance with the existing literature [5,6,10,11,19,20,[22][23][24].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In this first performance evaluation study, VIDAS ® anti-CHIKV IgM and IgG results were comparable to those of competitor IgM and IgG ELISAs, with positive and negative agreements between 97.5% and 100.0%. Given that existing commercial anti-CHIKV IgM and IgG ELISA are recognised for their ability to accurately detect anti-CHIKV antibodies [5,6,10,11,19,20,[22][23][24], our study, therefore, demonstrates the good clinical performance of the VIDAS ® anti-CHIKV IgM and IgG assays. Our study also confirmed the superior performance of ELISA over RDT, in accordance with the existing literature [5,6,10,11,19,20,[22][23][24].…”
Section: Discussionmentioning
confidence: 68%
“…Given that existing commercial anti-CHIKV IgM and IgG ELISA are recognised for their ability to accurately detect anti-CHIKV antibodies [5,6,10,11,19,20,[22][23][24], our study, therefore, demonstrates the good clinical performance of the VIDAS ® anti-CHIKV IgM and IgG assays. Our study also confirmed the superior performance of ELISA over RDT, in accordance with the existing literature [5,6,10,11,19,20,[22][23][24]. Moreover, the significant difference between the PPA of VIDAS ® and RDT assays (each compared to competitor ELISA) demonstrates for the first time the superior performance of VIDAS ® anti-CHIKV assays over that of RDT.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The Chikungunya virus (CHIKV) is considered an emerging pathogen that causes acute febrile illness (AFI) in many regions of Peru [ 8 ]. However, the prevalence of this pathogen may be underestimated due to its clinical similarity with other arboviral infections, such as DENV and ZIKV, which can circulate in the same geographical regions and are transmitted by the same vector [ 17 ]. One of the main limitations in these areas is the lack of access to reliable diagnostic tests, such as molecular and serological techniques; therefore, a study was conducted to evaluate the prevalence of CHIKV in febrile patients from the high jungle of the northern area of Peru.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other countries in Latin America report differing frequencies of this pathogen; for example, Lima et al [ 17 ] reported a prevalence of 3.84% of CHIKV cases among 182 patients, while a study in Puerto Rico that was conducted during a 3-year study period found that CHIKV corresponded to the 18.2% of the febrile patients [ 19 ]. These differences are related to various factors, among which are the seasonality on which the volume of rainfall and temperature depend, and the use of serological techniques for diagnosis, since antibodies are detectable for a longer time [ 17 ]. It should be mentioned that the prevalence of CHIKV is heterogeneous among the different Latin American countries and even in different regions within the same country; therefore, molecular diagnosis is critical for the epidemiological surveillance of this virus [ 1 , 20 ].…”
Section: Discussionmentioning
confidence: 99%